To solve the inequality for x, we will need to simplify the equation. The first step is to distribute the 3 on the left side of the equation:
3(x-4) ≤ 8x + 13
3x - 12 ≤ 8x + 13
Now, we can subtract 3x from both sides:
-12 ≤ 5x + 13
To isolate x, we can subtract 13 from both sides:
-25 ≤ 5x
The resulting inequality is -25 ≤ 5x.
Use the inequality to answer the following question
3(x-4)≤8x+13
Which of the following inequalities could be the result of the first step in solving the inequality for x?
1 answer